2009
DOI: 10.1038/leu.2009.34
|View full text |Cite
|
Sign up to set email alerts
|

A novel AML-selective TRAIL fusion protein that is superior to Gemtuzumab Ozogamicin in terms of in vitro selectivity, activity and stability

Abstract: Gemtuzumab ozogamicin (GO, Mylotarg) is a targeted therapeutic agent in which an anti-CD33 antibody is chemically coupled to a highly cytotoxic calicheamicin derivative through a hydrolysable linker. GO has improved the treatment outcome for a subgroup of acute myeloid leukemia (AML) patients, but its use is associated with severe myelosuppression and hepatotoxicity. Here, we report on a novel anti-leukemia agent, designated scFvCD33:sTRAIL, in which an anti-CD33 single chain fragment of variable regions (scFv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Several previous studies have reported the targeting of primary AML cells using reagents that bind CD33 41,42 or CD64, 32,43 but these have not focused on the treatment of CMML or AMML. The development of targeted therapeutics for these diseases is restricted by the lack of specific genetic aberrations that can be influenced by small molecules or antibodies and the lack of useful in vitro and in vivo disease models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported the targeting of primary AML cells using reagents that bind CD33 41,42 or CD64, 32,43 but these have not focused on the treatment of CMML or AMML. The development of targeted therapeutics for these diseases is restricted by the lack of specific genetic aberrations that can be influenced by small molecules or antibodies and the lack of useful in vitro and in vivo disease models.…”
Section: Discussionmentioning
confidence: 99%
“…The granzyme B constructs were less potent towards primary cells than cell lines, as previously reported for primary AML cells. 41,42,45 This reflects the mixed lineage of CMML cells, with only part of the cell population derived from the CD64 1 monocytic lineage and others derived from CD64 -progenitors. The CD64-dependent enrichment of target cells was not feasible because the receptor would be blocked.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of valproic acid or mitoxantrone could also improve the efficacy of cell killing because these chemicals have already been shown to enhance the toxicity of specific immunotoxins. 7 Because ETA' is prokaryotic in origin, repetitive administration is likely to result in an undesirable immune response, which would limit the therapeutic use of the immunotoxin. 22 This could be avoided by replacing the cytotoxic component with human proapoptotic proteins, such as granzyme B/M, angiogenin, DAPK2 and Tau, to form fully human constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these developments, most attention is still focused on a calicheamicin-coupled CD33-targeting antibody, gemtuzumab ozogamicin (Mylotarg Ò ), which was approved by the Food and Drug Administration in 2000 for the treatment of patients 60 years of age and older with recurrent AML, who were not considered candidates for standard chemotherapy. 7 The drug was withdrawn in 2010 due to new safety concerns and the product's failure to show clinical benefit to patients enrolled in a confirmatory trial conducted after approval. 8 The main drawback of the antigens listed above is that they are not exclusive to AML cells and are also presented on normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used leukemic stem cell (LSC) marker in the study of AML treatment is CD33 (13,14). It has also made it as far as to gain FDA approval and Anti-CD33 antibodies have become a significant aspect of CSC targeted therapy (15,16). A CD33 based therapy, named Mylotarg, which combines calicheamicin (a cytotoxic antibiotic) with an anti-CD33 antibody, was approved by the FDA in 2000 (17).…”
Section: Previously Considered Clinical Implications Of Cscs: 311 mentioning
confidence: 99%